Проблеми відшкодування шкоди, завданої в результаті дорожньо-транспортних пригод - Харитонов, Євген Олегович; Харитонов, Є. О.; Kharytonov, Yevhen O.; Харитонова, Олена Іванівна; Харитонова, О. І.; Kharytonova, Olena I. (Одеса, 2018)
У статті розглядаються питання відшкодування шкоди, завданої в результаті дорожньо-транспортних пригод, зі встановленням при цьому загальних засад відшкодування шкоди, завданої під час використання транспортних засобів (автомобілів), а також особливостей відшкодування шкоди, завданої під час використання автомобілів.

Still in Ukraine, on average, 9 people die because of road accidents every day. However, our country does not belong to the leaders of automobile production, therefore, the best way to solve the problem of increasing road safety is not technical innovations, but effective use of organizational and legal means. Ukraine does not have a special law that specifically regulates civil relations arising as a result of car accidents. Instead, in such cases, the norms of the Civil Code of Ukraine are applied, which, however, require additional interpretation. The article deals with the issues of compensation for damage caused as a result of road accidents, with establishing the general principles of compensation for damage caused by the use of vehicles, as well as the peculiarities of compensation for damage caused by using vehicles. Since there is no direct indication in the law of what kinds of activities, concerning which objects and in which cases there is an increased danger, the definition of the signs of such a source becomes important. In particular, their inclusion gives an opportunity to determine in which cases, activities related to cars can be considered a source of increased danger. The duty to compensate for the damage caused by the car rests with its owner. Not recognized as owner and does not reimburse the person who ran the car while performing his work duties. However, when such a person has used the car for personal use without permission, it is an unlawful takeover and this person is obliged to compensate the damage caused on the general grounds. According to Part 5 of Article 1187 of the Civil Code of Ukraine, a person who carries out activities that are a source of increased danger is liable for the damage, unless he proves that the damage was caused by the force majeure or the victim’s intent. The study leads to the conclusion that the peculiarities of compensation for damage caused by traffic accidents are determined by the fact that activities related to the use of cars are a source of increased danger. This determines the peculiarities of the definition of the subjects of compensation, the conditions for the occurrence of relevant obligations and the grounds for exemption from liability.
Харитонов Є. О. Проблеми відшкодування шкоди, завданої в результаті дорожньо-транспортних пригод / Є. О. Харитонов, О. І. Харитонова // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Одеса, 2018. – Вип. 31. – С. 6-14.
Keywords: дорожньо-транспортні пригоди; транспортні засоби; автомобілі; джерело підвищеної небезпеки; відшкодування; відповідальність; road accidents; vehicles; cars; source of increased danger; compensation; liability; Research Subject Categories::LAW/JURISPRUDENCE